ANALISIS EFEKTIVITAS MEDIASI SEBAGAI MEKANISME PENYELESAIAN SENGKETA HAK CIPTA LAGU BERDASARKAN ALTERNATIF PENYELESAIAN SENGKETA - NIM. A1012211003, BARTOLOMIUS NOVIANTO (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract In today's digital era, the music industry is undergoing a significant transformation, especially with the ease of access and distribution of works through online platforms. However, this convenience also brings new challenges, especially in terms of copyright protection. Therefore, researchers are interested in analyzing the title